Applying economic incentives to increase effectiveness of an outpatient weight loss program (TRIO) – A randomized controlled trial. (July 2017) - Finkelstein, Eric A.; Tham, Kwang-Wei; Haaland, Benjamin A.; Sahasranaman, Aarti
Abstract: The prevalence of overweight and obesity has more than doubled in the past three decades, leading to rising rates of non-communicable diseases. This study tests whether adding a payment/rewards (term reward) program to an existing evidence-based weight loss program can increase weight loss and weight loss maintenance. We conducted a parallel-group randomized controlled trial from October 2012 to October 2015 with 161 overweight or obese individuals randomized to either control or reward arm in a 1:2 ratio. Control and reward arm participants received a four month weight loss program at the LIFE (Lifestyle Improvement and Fitness Enhancement) Centre at Singapore General Hospital. Those in the reward arm paid a fee of S165.00 (1US = 1.35S) to access a program that provided rewards of up to S660 for meeting weight loss and physical activity goals. Participants could choose to receive rewards as guaranteed cash payments or a lottery ticket with a 1 in 10 chance of winning but with the same expected value. The primary outcome was weight loss at months 4, 8, and 12. 161 participants were randomized to control (n = 54) or reward (n = 107) arms. Average weight loss was more than twice as great in the reward arm compared to the control arm at month 4 when the program concluded (3.4 kg vs 1.4 kg, p < 0.01), month 8 when rewards concluded (3.3 kg vs 1.8 kg, p < 0.05), and at month 12 (2.3 kg vs 0.8 kg, p < 0.05). These results reveal that a payment/rewards program can be used to improve weight loss and weight loss maintenance when combined with an evidence-based weight loss program. Future efforts should attempt to replicate this approach and identify how to cost effectively expand these programs to maximize their reach. This study is registered atwww.clinicaltrials.gov (Identifier: NCT01533454). Highlights: A novel payment/rewards program to improve weight loss outcomes was tested via an RCT. Rewards participants paid S165 to access rewards of up to S660 for meeting goals. Over 12 months, weight loss in the rewards arm was double that among controls.